Estrogen Receptor α Regulates Ethanol Excitation of Ventral Tegmental Area Neurons and Binge Drinking in Female Mice - Vandegrift, Bertha J. (J Neurosci, 2020)
Elevations in estrogen (17β-estradiol, E2) are associated with increased alcohol drinking by women and experimentally in rodents. E2 alters the activity of the dopamine system, including the VTA and its projection targets, which plays an important role in binge drinking. A previous study demonstrated that, during high E2 states, VTA neurons in female mice are more sensitive to ethanol excitation. However, the mechanisms responsible for the ability of E2 to enhance ethanol sensitivity of VTA neurons have not been investigated. In this study, we used selective agonists and antagonists to examine the role of ER subtypes (ERα and ERβ) in regulating the ethanol sensitivity of VTA neurons in female mice and found that ERα promotes the enhanced ethanol response of VTA neurons. We also demonstrated that enhancement of ethanol excitation requires the activity of the metabotropic glutamate receptor, mGluR1, which is known to couple with ERα at the plasma membrane. To investigate the behavioral relevance of these findings, we administered lentivirus-expressing short hairpin RNAs targeting either ERα or ERβ into the VTA and found that knockdown of each receptor in the VTA reduced binge-like ethanol drinking in female, but not male, mice. Reducing ERα in the VTA had a more dramatic effect on binge-like drinking than reducing ERβ, consistent with the ability of ERα to alter ethanol sensitivity of VTA neurons. These results provide important insight into sex-specific mechanisms that drive excessive alcohol drinking. SIGNIFICANCE STATEMENT Estrogen has potent effects on the dopamine system and increases the vulnerability of females to develop addiction to substances, such as alcohol. We investigated the mechanisms by which estrogen increases the response of neurons in the VTA to ethanol. We found that activation of the ERα increased the ethanol-induced excitation of VTA neurons. 17β-Estradiol-mediated enhancement of ethanol-induced excitation required the metabotropic glutamate receptor mGluR1. We also demonstrated that ERs in the VTA regulate binge-like alcohol drinking by female, but not male, mice. The influence of ERs on binge drinking in female mice suggests that treatments for alcohol use disorder in women may need to account for this sex difference.